Never Letting a Good Crisis Go to Waste: Canadian Interdiction of Asylum Seekers - Rehaag, Sean; Song, Janet; Toope, Alexander (Frontiers in Human Dynamics, 2020)
This article examines two moments of crisis at Canada’s border with the United States: the aftermath of September 11th, 2001 and the COVID-19 pandemic. The Canadian government leveraged both crises to offshore responsibilities for refugees onto the US. In the first case, Canada took advantage of US preoccupations with border security shortly after 9/11 to persuade the US to sign the Canada-US Safe Third Country Agreement (“STCA") – an agreement that allows Canada to direct back asylum seekers who present themselves at ports-of-entry on the Canada-US border. In the second case, Canada used heightened anxieties about international travel during the COVID-19 pandemic to persuade the US to block irregular border crossings that asylum seekers were increasingly using to circumvent the STCA. After reviewing Canada’s successful use of these moments of crisis to persuade the US to take on additional responsibilities for refugees for whom Canada would have otherwise been responsible, the article discusses a recent Canadian Federal Court decision that may make all this political maneuvering moot. This decision found that Canada cannot send asylum seekers back to the US without violating constitutional rights to life, liberty, and security of the person. Given past practice, however, we can expect the Canadian government to continue to pursue avenues to persuade the US to take on additional responsibility for refugees – and moments of crisis will be important drivers for those efforts.